Flint awls at the Mesolithic site of Star Carr: Understanding tool use through integrated methods. (June 2022) - Bates, Jessica; Needham, Andy; Conneller, Chantal; Milner, Nicky; Pomstra, Diederik; Little, Aimée
Highlights: Awls from Star Carr were analysed using GIS, microwear and experimental archaeology. GIS revealed clusters of awls to the west of the site, many of which were utilised. Microwear indicates awls were used to work bone, soft mineral, hide, and wood. Experimental archaeology revealed insights into awl tip changes during use. The approach augments awl typology, enabling assessment of tool form vs. use. Abstract: The form and macroscopic wear of Mesolithic awls has been used to infer function, which has become an aspect of established typologies. However, verification of form/function relationships are needed to ensure typologies are robust. This paper presents the results of GIS and microwear analysis of 54 flint awls excavated from the Early Mesolithic site of Star Carr, UK, in conjunction with results from experimental research on awl use. Results expand on previous findings that awls were used for a range of activities at Star Carr, reflected in the different worked contact materials identified; including mineral, wood, bone, and hide. The experimental programme provided important insights into macroscopic tip modification of awls working with different contact materials for different lengths of time. Rates of tip snapping were found to be high in the Star Carr sample. GIS plots of awl location integrated alongside the microwear results show that the majority of awls were recovered from the west of the site, with clusters composed of different contact materials. The proximity of hide and shale working may suggest the production of clothing with appliqué beads. The combination of microwear, experimental archaeology, and GIS is applicable to other Mesolithic sites and holds potential to expand our knowledge of the spatial structuring of tool-using behaviours. Moreover, combined use of these methods has enabled greater understanding of awl typologies: providing a means to independently assess the relationship between tool morphology and use.